BEYOND GENDER MAINSTREAMING: RECLAIMING THE BEIJING PLATFORM FOR ACTION IN INDONESIA’S RPJMN 2025–2029 - Rizky Bangun Wibisono (ipdn, 2025)
This article examines Indonesia’s National Medium-Term Development Plan (RPJMN) 2025–2029 within the broader vision of Indonesia Emas 2045 through a feminist policy analysis lens. Addressing the gap between global normative commitments to gender equality particularly the Beijing Platform for Action (BPfA) and national development planning practices, the article argues that the RPJMN 2025–2029 reproduces an instrumental and technocratic form of gender mainstreaming. Drawing on qualitative analysis of policy documents, the findings reveal that gender is treated as a policy add-on rather than as a framework for structural justice. This pattern manifests consistently across four key domains: poverty reduction, industrial development and land conflict, climate change, and the Indonesia Emas 2045 vision. In each domain, women are positioned as program targets, vulnerable groups, or human capital resources, while power relations, unpaid care work, and women’s agency are largely absent from policy analysis. The article demonstrates that these limitations reflect a single pattern of structural failure rather than isolated sectoral shortcomings. By reclaiming the BPfA as a feminist development roadmap, this study calls for a shift from gender as an instrument of development toward gender as a transformative foundation for social justice and equitable power relations.Keywords: RPJMN, Beijing Platform for Action, Gender and Development.